Numerical modeling of the impact on water of a flexible structure by explicit finite element method — Comparisons with Radioss numerical results and experiments - Ribet, H; Laborde, P; Mahé, M (Aerospace science and technology, 1999)
The current development of crash calculation codes associated with the significant improvement in the performance of data processing facilities allow us to consider, in an industrial framework and under interesting economical conditions, numerical simulations of the impact on water of a deformable structure. A transient fast dynamic finite element method has been chosen for its potential to model the nonlinearities of the structure, geometrical, material or contact nonlinearities. It is evaluated here for various test cases for which the analytical and numerical results are available. The correlations between calculations and reference results, and their costs, allow such an approach to be validated subject to a definitive validation on a representative structure. Le développement actuel de codes de calcul de crash associé à l'amélioration significative des performances des moyens informatiques permettent d'envisager, dans un cadre industriel et à des conditions économiques intéressantes, des simulations numériques d'impact sur l'eau de structure déformable. Une méthode par éléments finis explicite de dynamique rapide transitoire a été choisie pour ses potentialités à modéliser les non-linéarités de la structure, non-linéarités géométriques, matérielles ou de contact. Elle est évaluée ici à partir de différents cas tests pour lesquels résultats analytiques et numériques sont disponibles. Les corrélations entre calculs et résultats de référence, ainsi que leur coût, permettent de valider une telle approche, sous réserve d'une validation définitive sur une structure représentative.